Targeting LOXL2 for cardiac interstitial fibrosis and heart failure treatment - Jin Yang (Nature Portfolio, 2016)
Lysyl oxidase-like 2 (LOXL2) is an enzyme that promotes scaffolding of extracellular matrix proteins. Here the authors show that LOXL2 is crucial for pressure-overload induced cardiac fibrosis, and that antibody-mediated inhibition or genetic disruption ofLoxl2in mice shows therapeutic potential for treatment of cardiac fibrosis.